Implikasi Covid-19 Terhadap Nilai Kesusilaan Perspektif Teologi Moral - I Wayan Sunampan Putra (Sphatika: Jurnal Teologi, 2021)
The Phenomenon of Covid-19 is one of the problems faced by the public. This can be seen in most busy countries to deal with the spread of Covid-19. Various ways are done to limit or reduce its spread. Such rapid dissemination causes fear and unrest in people's lives, both physically and psychically. This paper aims to outline the implications of Covid-19 in every human life. Also, the spread of Covid-19 has a profound impact on people's lives in various aspects such as economic growth, social relations, and moral issues. Maanfaat from this paper that provides an overview of the implications on the value of decency, so that it can be used as a reprensi in finding solutions to handling Covid-19.